Economic theory in a changing world policymaking for growth - Lahiri Sajal; Maiti Pradip (Oxford OUP, 2005)
This volume brings together thirteen essays - written by well-known academics across three continents - on economic growth and development from theoretical and empirical perspectives. The essays are wide-ranging and cover both classical and neoclassical
Keywords: Economic growth; Economic policy